2021
DOI: 10.1111/jcmm.16476
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 attenuates proliferative vitreoretinopathy and epithelial‐mesenchymal transition of retinal pigment epithelial cells via wnt/β‐catenin pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Similarly, Dickkopf‐1 (DKK1) can reduce the osteogenic potential of BMSCs and cause bone loss 31,32 . Previous studies have shown that Mettl3 could regulate the Wnt/β‐catenin pathway 33,34 . However, the regulatory mechanism of Mettl3 influences the bone differentiation of OP‐BMSCs through the canonical Wnt pathway is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dickkopf‐1 (DKK1) can reduce the osteogenic potential of BMSCs and cause bone loss 31,32 . Previous studies have shown that Mettl3 could regulate the Wnt/β‐catenin pathway 33,34 . However, the regulatory mechanism of Mettl3 influences the bone differentiation of OP‐BMSCs through the canonical Wnt pathway is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the possible mechanism of MTDH regulating EMT, given that m6A RNA methylation is crucial for promoting EMT in cancer ( Chen et al., 2020 ; Jin et al., 2020 ; Lin et al., 2019 ; Ma et al., 2021 ; Xu et al., 2021 ), the correlation between m6A RNA methylation and MTDH was performed. As shown in Figures 6 A–6H, the estimated score of m6A RNA methylation was significantly correlated with MTDH expression in BLCA (R = 0.6, p < 0.01), BRCA (R = 0.54, p < 0.01), CHOL (R = 0.73, p < 0.01), LUAD (R = 0.43, p < 0.01), HNSC (R = 0.53, p < 0.01), KIRC (R = 0.5, p < 0.01), KIRP (R = 0.64, p < 0.01), and LIHC (R = 0.47, p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…m6A RNA methylation is crucial for the regulation of EMT through WNT/beta-catenin, PI3K/Akt, LAST2/YAP pathway, or Sox4 mRNA stability ( Chen et al., 2020 ; Jin et al., 2020 ; Lin et al., 2019 ; Ma et al., 2021 ; Xu et al., 2021 ). Our study showed that the most differential genes in the high expression of MTDH tumor might be enriched in the activation of the PI3K/Akt pathway, indicating MTDH may regulate PI3K/Akt-induced EMT by m6A RNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple agents are being investigated in preclinical in vitro and in vivo studies. Agents that inhibit RPE cell proliferation, migration, and EMT by targeting TGFb or the TGFb-signaling cascade, including Runt-related transcription factor 1 (RUNX1) inhibitors [50 && ], protein kinase A inhibitors [53], Smad signaling inhibitors [45,54], METTL3 overexpression [55], p38 inhibition [46,56], and micro-RNA approaches. Other therapeutic targets being investigated include inhibition of epidermal growth factor [57,58], FGF [59], and rho kinase [60 && ].…”
Section: Novel Targets For Proliferative Vitreoretinopathy Inhibitionmentioning
confidence: 99%